Eco-friendly one-pot synthesis of ultradispersed TiO2 nanocrystals/graphene nanocomposites with high photocatalytic activity for dye degradation. Issue 39 (7th September 2015) - Shao, Penghui; Tian, Jiayu; Shi, Wenxin; Gao, Shanshan; Cui, Fuyi
Abstract : We report an eco-friendly one-pot hydrothermal synthesis of ultrafine TiO2 nanocrystals (∼4.01 nm) homogeneously dispersed on the entire surface of graphene. Abstract : We report an eco-friendly one-pot hydrothermal synthesis of ultrafine TiO2 nanocrystals (∼4.01 nm) homogeneously dispersed on the entire surface of graphene. Two specific contributions of glycerol, as the inhibitor to confine the growth and aggregation of primary TiO2 nanoparticles and as the spacer to hinder the restacking of graphene nanosheets, for building the unique TiO2 /graphene nanoarchitectures have been clarified based on the systematic investigations. Compared with TiO2 /graphene hybrids synthesized without glycerol and commercial P25, the ultradispersed TiO2 nanocrystals/graphene nanocomposites synthesized with the addition of glycerol have exhibited much higher photocatalytic activity for degradation of rhodamine B and methylene blue under visible light irradiation. The excellent recyclability and physicochemical stability of the as-synthesized nanocomposites have also been verified by the cycling photodegradation tests. The high photocatalytic activity and excellent stability of the as-synthesized nanocomposites are mainly attributed to the very high surface area (∼452 m 2 g −1 ), efficient charge separation, and improved visible light absorbance, which originate from the advantageous nanoarchitectures such as ultradispersed and ultrasmall nature of TiO2 nanocrystals as well as the intimate and maximum contact interfaces between TiO2 and graphene.